2010
DOI: 10.5194/hess-14-1773-2010
|View full text |Cite
|
Sign up to set email alerts
|

Towards the sequential assimilation of SAR-derived water stages into hydraulic models using the Particle Filter: proof of concept

Abstract: Abstract. With the onset of new satellite radar constellations (e.g. Sentinel-1) and advances in computational science (e.g. grid computing) enabling the supply and processing of multimission satellite data at a temporal frequency that is compatible with real-time flood forecasting requirements, this study presents a new concept for the sequential assimilation of Synthetic Aperture Radar (SAR)-derived water stages into coupled hydrologic-hydraulic models. The proposed methodology consists of adjusting storages… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
108
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(111 citation statements)
references
References 43 publications
2
108
0
Order By: Relevance
“…Particle filter assimilation is a Bayesian learning system which accounts for input data uncertainty propagation by selecting suitable input data from randomly generated ones without assuming any particular distribution of their PDF (Noh et al, 2011). The particle filter technique was used in studies like Matgen et al (2010) and Giustarini et al (2011), where input data are in the form of ensemble flow outputs of a hydrological model. In Giustarini et al (2011) to assimilate water levels derived from two SAR images of flooding in the Alzette River into a hydraulic model, 64 upstream flows were generated from an ensemble hydrologic model and used as the upstream boundary conditions.…”
Section: Z N Musa Et Al: a Review Of Applications Of Satellite Sarmentioning
confidence: 99%
See 1 more Smart Citation
“…Particle filter assimilation is a Bayesian learning system which accounts for input data uncertainty propagation by selecting suitable input data from randomly generated ones without assuming any particular distribution of their PDF (Noh et al, 2011). The particle filter technique was used in studies like Matgen et al (2010) and Giustarini et al (2011), where input data are in the form of ensemble flow outputs of a hydrological model. In Giustarini et al (2011) to assimilate water levels derived from two SAR images of flooding in the Alzette River into a hydraulic model, 64 upstream flows were generated from an ensemble hydrologic model and used as the upstream boundary conditions.…”
Section: Z N Musa Et Al: a Review Of Applications Of Satellite Sarmentioning
confidence: 99%
“…Barneveld et al (2008) applied the same method and models for flood forecasting on the Rhine River and produced good results of 10-day forecasts; therefore assimilating data for natural catchments results in better forecast model values. More information on hydrologic data assimilation techniques can be found in Matgen et al (2010), Chen et al (2013) and García-Pintado et al (2015).…”
Section: Z N Musa Et Al: a Review Of Applications Of Satellite Sarmentioning
confidence: 99%
“…Though these studies have shown that the EnKF is a valuable tool for data assimilation in many applications, this study focuses on the use of the Particle Filter (PF). According to recent studies, the PF is an effective hydrologic and hydraulics data assimilation method, providing predictive uncertainty in model states, parameters and fluxes (DeChant and Moradkhani, 2011a, b;Matgen et al, 2010;Leisenring and Moradkhani, 2010;Moradkhani et al, 2005b;Montzka et al, 2011;Rings et al, 2010;Weerts and El Serafy, 2006). The PF is not subject to the limitations experienced in the EnKF including the Gaussian assumption of joint distribution of observation and model states and the linear updating of model states (Moradkhani et al, 2005b;Moradkhani and Sorooshian, 2008).…”
Section: Data Assimilation Using the Particle Filtermentioning
confidence: 99%
“…The potential of assimilating distributed value of water level from remote sensing for improved discharge and water depth estimation has been explored in different studies (e.g. Andreadis et al, 2007;Neal et al, 2007;Hostache et al, 2010;Matgen et al, 2010;Biancamaria et al, 2011;Giustarini et al, 2011;Mason et al, 2012;García-Pintado et al, 2013;Andreadis and Schumann, 2014) and a detailed review is presented by Schumann et al (2009) and Yan et al (2015).…”
Section: Introductionmentioning
confidence: 99%